POTENSI SOSIAL BUDAYA MASYARAKAT LOKAL SEBAGAI DAYA TARIK WISATA DI DESA WISATA GAMTALA DI JAILOLO KABUPATEN HALMAHERA BARAT - DJUHAERY, ASTRI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Tourist Village of Gamtala is one of the tourist village that located in Jailolo, West Halmahera Regency, North Maluku Province. This village offers many tours such as nature, culture, history tour. Society of Gamtala village are social society. There are various of social cultural forms of the society that potential as a tourism attractions. However, the existence of social culture held not to be taken seriously by the regional Government. The level of public awareness of the village with its potential is very low. The aims of this research is to identify of social culture elements which can be used as an tourism attractions in Gamtala Village. This research conducted by descriptive qualitative with the focus on questions and observations. Data obtained through interview, observation, and documentation technique which aims to identify social culture potentials held by the society of Gamtala Village. Then after that, be judged from the aspect of uniqueness, beauty, religious, and scientific. The result of the research shows that, there are several social culture that can potential as a tourism attractions, such as Crop Harvest Festival, "Horum Toma Sasadu" eating custom, mutual aid (babari), customary punishment, and local language. These five potentials, of course, each has strength and weakness, and obstacles in implementation. Some social cultural potentials that has been identified, it is not entirely meet the four aspects is meant. Therefore, mature strategy is needed to increase its quality as a tourism attractions. Keywords: social culture potentials, tourism attractions